MORPHOFUNCTIONAL CHARACTERISTICS OF THE LOWER HINDLIMB AND FOOT MUSCLES OF BORNEAN ORANGUTAN (Pongo pygmaeus) - Kartjito, Nicolas Edward Christanto; Kadarusman, Ikhsan; Novelina, Savitri; Nisa, Chairun; Laila, Sri Rahmatul; Cahyadi, Danang Dwi; Nurhidayat, Nurhidayat (Universitas Syiah Kuala, 2022)
Orangutan is a great ape that has anatomical and physiological aspects similar to those of gorillas and chimpanzees, although orangutan is more arboreal than other great apes. This research aims to study the morphofunctional characteristics of the lower hindlimb and foot muscles of Bornean orangutan and its relation to the type of locomotion and daily behavior. This research was conducted on the right leg of a male orangutan by observing the morphology of the lower hindlimb and foot muscles and observing the behavior of the Bornean orangutan through video observations. The results showed that digital flexor muscles are more developed than plantar flexor muscles as an adaptation towards arboreal activities that require finger flexor movements such as gripping tree branches. Orangutans have rudimentary hallux, which is related by the less developed intrinsic muscle and indicated by the way orangutan grips tree branches dominantly using digits II-V. At a certain time, male Bornean orangutans are active on terrestrial that causes the digital extensor muscles to have more developed as an adaptation to terrestrial activity. It can be concluded the morphology of the lower hindlimb and foot muscles is in accordance to its function and behavior adaptation in arboreal and terrestrial.